Clinical features of gastroesophageal reflux disease in children with different genotypes of C825T polymorphic loci of GNB3 gene - Dats-Opoka, Marta; Makukh, Halyna (Journal of Medical Science, 2017)
Introduction. Considering the steady growth of the gastroesophageal reflux disease (GERD) in children in recent decades, the difficulty of GERD diagnosing in children, the variety of GERD clinical and morphological features as well as the factors that cause it, including genetic predisposition, a detailed analysis of each of them remains relevant.Aim. To analyze the peculiarities of nutritional status in children with GERD and its correlation with the different genotypes of C825T polymorphic loci of GNB3 gene as well as its association with different GERD clinical manifestations.Material and Methods. The analysis of GERD clinical features was carried out and the nutritional status in 100 children of school age was estimated. Molecular and genetic research of C825T loci of GNB3 gene using PCR method (rs5443) was carried out in the studied group (100 children) and in 40 healthy children that formed the control group.Results. The distribution of the genotypes of C825T polymorphic loci of the GNB3 gene in children with GERD and healthy children in the control group did not have any statistically significant difference (?2 = 0.27, ? = 0.87). Among more than a half of the children in both groups, the GNB3 825ST heterozygous genotype were detected (54.0% of the experimental group and 57.5% of the control group), according to de Vries et al. data is a factor of GERD increased risk. The association between the genotype of C825T locus of GNB3 gene and the data of intragastric endoscopy with pH monitoring was found: in patients with hyperacidic GERD the genotype 825CT was predominantly revealed, and in children with normal and hypoacidic GERD a higher frequency of the 825TT genotype was found. In children with GERD having a lack of the nutritional status (61%), the genotype 825CT (61.82%, p = 0.013) and 825TT (100%, p = 0.005) of the GNB3 gene were detected significantly more often.Conclusions. The distribution of the genotypes of C825T polymorphic loci of the GNB3 gene in children with GERD was determined. Differences in GERD development depending on the different GNB3 genotypes were not detected. The distribution of the genotypes of C825T loci of the GNB3 gene remained unchanged at different GERD clinical manifestations. The presence of 825CT and 825TT genotypes of GNB3 gene in patients with GERD is associated with a decrease in physical development signs. The association between genotype of C825T loci of GNB3 gene and pH intragastric endoscopy data was identified: in patients with hyperacidity GERD 825CC genotype was usually found, and in children with normal- and hypoacidity GERD 825TT genotype was usually found.